Analisa Konsep Motivasi, dalam Peranannya untuk Menuju Sukses Meraih Cita-Cita, di Lingkungan Pondok Pesantren Alif Laam Miim Surabaya, dengan Metode Participatory Action Research - NM, Siti Rahayu (Proceedings of Annual Conference on Community Engagement, 2022)
This paper is entitled "Analysis of the Concept of Motivation, in Its Role Towards Success to Achieving Goals, in the Pondok Pesantren Aliif Laam Miim Surabaya, with the PAR Method". Is a form of community service to implement the concept of motivation which is analyzed to be applied in the Aliif Laam Miim Islamic Boarding School environment. Devotion started from the writer’s interest in the existence of the cottage, about how the cottage was originally established. According to the concept of motivation, it is certain that the cottage was built with a high motivation from its founders. The high motivation of the founders, according to the author, should not stop but must be contagious, spreading widely to various elements of the cottage. For this reason, this service is very suitable to use the PAR method. This PAR method involves many elements, namely the founding elements of the Pondok, school leaders, homeroom teachers, BP teachers, teachers. Furthermore, the results of the study found that in the field there were behavioral facts, that there were several students who had shown changes and increased motivation.